# Answer on Algebra Question for ashley

Question #10809

simplify the expressions:

8+3(-6)/3-(-7)

8+3(-6)/3-(-7)

Expert's answer

8+3(-6)/3-(-7) =8-6+7=9

though if you ment { 8+3(-6) }/{3-(-7)} (i.e. it's a fraction)

then { 8+3(-6) } / {3-(-7)}={8-18}/{3+7}=-1

though if you ment { 8+3(-6) }/{3-(-7)} (i.e. it's a fraction)

then { 8+3(-6) } / {3-(-7)}={8-18}/{3+7}=-1

Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment